Effect of Berberine from Coptis chinensis on Apoptosis of Intestinal Epithelial Cells in a Mouse Model of Ulcerative Colitis: Role of Endoplasmic Reticulum Stress. (25th April 2020) - Yan, Shen; Yingchao, Liu; Zhangliu, Wang; Xianli, Ruan; Si, Li; Siyi, Ni; Jihong, Zhong
Abstract : The purpose of this study was to verify the effect of berberine (BBR) on endoplasmic reticulum stress (ERS) and apoptosis of intestinal epithelial cells (IECs) in mice with ulcerative colitis (UC). BALB/c mice were randomly divided into five groups as follows: blank control, model, and low-, medium-, and high-dose BBR. A dextran sodium sulfate- (DSS-) induced model of UC was prepared, and the low-, medium-, and high-dose BBR groups were simultaneously gavaged with a BBR suspension for 7 d. Disease activity index (DAI) was assessed, and tissue damage index (TDI) was assessed from colon samples after the last administration. TUNEL assays were used to detect apoptosis of IECs. Immunohistochemistry and/or real-time PCR were applied to determine the expression of GRP78, caspase-12, and caspase-3. In all BBR treatment groups, clinical symptoms of colitis and histopathological damage were significantly reduced. The high-dose BBR group exhibited particularly pronounced decrease (p < 0.01 ) in both DAI (0.48 ± 0.36) and TDI (1.62 ± 0.64) relative to the model group (1.50 ± 0.65 and 3.88 ± 0.04, respectively). In colon tissues of the model group, the number of apoptotic IECs was significantly increased; the expression of GRP78, caspase-12, and caspase-3 proteins was significantly increased; and the expression of the GRP78 mRNA was upregulated. In low-, medium-, and high-dose BBR groups, the number of apoptotic IECs was significantly reduced. Moreover, GRP78 and caspase-3 expression levels were significantly decreased in the medium- and high-dose BBR groups, caspase-12 expression was significantly decreased in the high-dose BBR group, and the GRP78 mRNA expression level was significantly decreased in the high-dose BBR group. BBR can effectively reduce the rate of IEC apoptosis in UC mice and alleviate the inflammatory response in the colon. The underlying mechanism seems to involve ERS modulation and inhibition of ERS-mediated activation of the caspase-12/caspase-3 apoptosis signaling pathway.